The Preliminary Study on the Comparative Assessment of Carbon Stock Related to Changes in Land Use in Phuket and Phayao Provinces - EVA NOVITA SARI (Prince of Songkla University, 2022)
Thesis (M.Sc., Earth System Science)--Prince of Songkla University, 2019